Comparison of pain behaviour and osteoarthritis progression between anterior cruciate ligament transection and osteochondral injury in rat models - Tawonsawatruk, T. (Bone Joint Res, 2018)
OBJECTIVES: In this study, we compared the pain behaviour and osteoarthritis (OA) progression between anterior cruciate ligament transection (ACLT) and osteochondral injury in surgically-induced OA rat models. METHODS: OA was induced in the knee joints of male Wistar rats using transection of the ACL or induction of osteochondral injury. Changes in the percentage of high limb weight distribution (%HLWD) on the operated hind limb were used to determine the pain behaviour in these models. The development of OA was assessed and compared using a histological evaluation based on the Osteoarthritis Research Society International (OARSI) cartilage OA histopathology score. RESULTS: Both models showed an increase in joint pain as indicated by a significant (p < 0.05) decrease in the values of %HLWD at one week post-surgery. In the osteochondral injury model, the %HLWD returned to normal within three weeks, while in the ACLT model, a significant decrease in the %HLWD was persistent over an eight-week period. In addition, OA progression was more advanced in the ACLT model than in the osteochondral injury model. Furthermore, the ACLT model exhibited a higher mean OA score than that of the osteochondral injury model at 12 weeks. CONCLUSION: The development of pain patterns in the ACLT and osteochondral injury models is different in that the OA progression was significant in the ACLT model. Although both can be used as models for a post-traumatic injury of the knee, the selection of appropriate models for OA in preclinical studies should be specified and relevant to the clinical scenario. Cite this article: T. Tawonsawatruk, O. Sriwatananukulkit, W. Himakhun, W. Hemstapat. Comparison of pain behaviour and osteoarthritis progression between anterior cruciate ligament transection and osteochondral injury in rat models. Bone Joint Res 2018;7:244–251. DOI: 10.1302/2046-3758.73.BJR-2017-0121.R2.